2007
DOI: 10.1038/nnano.2007.39
|View full text |Cite
|
Sign up to set email alerts
|

Applications of dip-pen nanolithography

Abstract: The ability to tailor the chemical composition and structure of a surface at the sub-100-nm length scale is important for studying topics ranging from molecular electronics to materials assembly, and for investigating biological recognition at the single biomolecule level. Dip-pen nanolithography (DPN) is a scanning probe microscopy-based nanofabrication technique that uniquely combines direct-write soft-matter compatibility with the high resolution and registry of atomic force microscopy (AFM), which makes it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
616
0
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 811 publications
(623 citation statements)
references
References 123 publications
0
616
0
4
Order By: Relevance
“…Given the total amount M, diffusion coefficient D, and critical concentration C 0 are all constants for a certain system, the second term, ln 2CðpDÞ 1=2 M , is also a constant. If we regard x 2 4t as the independent variable and À 1 2 lnðtÞ as the functional variable in equation [2], the diffusion coefficient, D, can be regarded as the inversion of slope in equation [2]. Since the difference between the well-ordered SAMs and EG 3 or EG 6 will only influence the concentration of EG 3 or EG 6 , C, in equation [2] and will not change the slope in this equation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the total amount M, diffusion coefficient D, and critical concentration C 0 are all constants for a certain system, the second term, ln 2CðpDÞ 1=2 M , is also a constant. If we regard x 2 4t as the independent variable and À 1 2 lnðtÞ as the functional variable in equation [2], the diffusion coefficient, D, can be regarded as the inversion of slope in equation [2]. Since the difference between the well-ordered SAMs and EG 3 or EG 6 will only influence the concentration of EG 3 or EG 6 , C, in equation [2] and will not change the slope in this equation.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, SAMs found wide applications in chemistry, physics, and especial biology [2][3][4][5] when SAMs combined with microfluidic technology [6][7][8][9][10]; for example, we applied alkanethiolate SAMs on gold surface to study the relationship between the shape of mammalian cells and their migration direction [11]. Recently, when we applied alkanethiolate SAMs combined with microfluidic technology to establish interaction models for multiple types of cells [12], we found that the SAMs diffused on the surfaces of evaporation-coated gold slides which were covered with polydimethylsiloxan (PDMS) stamps [13].…”
Section: Introductionmentioning
confidence: 99%
“…Dip-pen scanning probe lithography (dp-SPL) offers high resolution and registration with direct write patterning capabilities 106 . The lithography functions by facilitating the direct transport of molecules to surfaces, much like the transfer of ink from a macroscopic dip-pen to paper.…”
Section: Additional Spl Methodsmentioning
confidence: 99%
“…4,5 While many fabrication methods abound, 6 probebased techniques, such as dip pen 7 and fountain pen 8 lithography, electrospinning, 9 scanning electrochemical microscopy 10,11 and meniscus-based methods [12][13][14][15][16][17][18][19][20] offer exciting new ways to fabricate novel structures. Previous meniscus-based fabrication techniques 20 have made structures that have tended to make contact with a substrate at a limited number of points.…”
mentioning
confidence: 99%